2006
DOI: 10.1161/01.hyp.0000203308.52919.dc
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Supporting a Functional Role for Intracellular Renin in the Brain

Abstract: Abstract-The brain renin-angiotensin system is implicated in the regulation of blood pressure (BP) and fluid homeostasis.Recent studies reveal that 2 forms of renin are expressed in the brain of rodents and humans: secreted prorenin and a nonsecreted intracellular form of active renin (icREN). Although the intracellular action of renin has long been postulated, no data supporting its role in BP regulation has been reported. Therefore, we directly evaluated whether this form of renin has physiological implicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
72
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 42 publications
3
72
2
Order By: Relevance
“…[14][15][16][17][18][19] The potential role of intracellular Ang II could be traced back to an early study in which radiolabelled Ang II was found in the nuclei of vascular smooth muscle and cardiac cells following systemic administration. 20 However, Re [25][26][27] Haller et al showed that microinjection of Ang II directly into rat vascular smooth muscle cells increased intracellular calcium, which could be blocked by intracellular AT 1 -receptor blockers.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19] The potential role of intracellular Ang II could be traced back to an early study in which radiolabelled Ang II was found in the nuclei of vascular smooth muscle and cardiac cells following systemic administration. 20 However, Re [25][26][27] Haller et al showed that microinjection of Ang II directly into rat vascular smooth muscle cells increased intracellular calcium, which could be blocked by intracellular AT 1 -receptor blockers.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, central injection of AT 1 receptor antagonist, Losartan, blocks AT 1 receptors and influences on central angiotensin mechanisms [24,26]. Infusion of Ang II into a lateral cerebral ventricle produce an increase in blood pressure [27,20,28], increase in mean arterial pressure [29,30], decrease in urine flow [27], regulate hydromineral balance [22], induce the pressor response [31], stimulate AVP and OT release [20,28] and elevate RSNA (renal sympathetic nerve activity) [32]. Losartan blocks water intake in intracellular and extracellular dehydrated conditions, inhibits the release of AVP and OT, reduces RSNA response and antidiuretic action [5,32].…”
Section: Discussionmentioning
confidence: 99%
“…7 Since there was no information on regional distribution of expression of the human renin, different patterns for expression of intracellular versus secreted human renin may be responsible. Additionally, with intracellular human renin overexpression there was an increase in circulating mouse renin.…”
mentioning
confidence: 99%
“…An important issue raised by the Lavoie et al 7 article is relevant to glial versus neuronal origins of components of the brain RAS. Whether there are distinct actions of angiotensin peptides derived from either source remains an interesting area of active investigation.…”
mentioning
confidence: 99%
See 1 more Smart Citation